PERAN PEMBELAJARAN MENGGUNAKAN TUTOR TEMAN SEBAYA DALAM MENINGKATKAN PERILAKU REMAJA TENTANG PENDEWASAAN USIA PERKAWINAN - Putu Sri Erawati (Jurnal Skala Husada : The Journal of Health, 2017)
ABSTRACT: Based on Health Research Data in 2010 about early marriage found that Indonesian women married in the age about 10 to 14 years old 0,2%, and in the age 15 to 19 years old 11,7%. Those problem can be anticipated by giving the teenagers an education about maturation age of marriage. This research aims to notice the role of peer group teaching approach to increase teenagers behavior about maturation age of marriage system in teenagers organization of Abiansemal District, Badung Regency. This designed with Experiment Pretest and Posttest Control Group Design. The variables are knowledge, attitude, and practice about maturation age in marriage, with the interval scale. The data was collected by test, which are written test. There were 17 cases had been found. Sixs  cases were intervention group and 11 cases were control group. This research fount significan deferen betwine behavior about maturation age of marriage system in teenagers organization of Abiansemal District, Badung Regency.Teenagers behavior about maturation age of marriage system in case intervention group before and after learning (p=0,046).in case control group (p =0,005). Conclution the role of peer group in teaching approach to increase teenagers behavior about maturation age of marriage system in teenagers organization of Abiansemal District, BadungKey word : Peer group, Teenagers, behavior, Maturation age of marriage